2020
DOI: 10.1007/s00238-020-01730-z
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of aesthetic surgery in India, current practice scenario, and anticipated post-COVID-19 changes: a survey-based analysis

Abstract: Background The declaration of COVID pandemic by the WHO can certainly be seen as a watershed era the world has witnessed in modern times. All non-essential industries and services have taken a back seat including aesthetic medicine. Over the last decade, India has witnessed a steady growth in medical tourism owing to global standards of care and services at a relatively modest cost. The following study was conducted to ascertain the sea change that this pandemic has brought into aesthetic surgeons' practice, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In India, Sangeeta Thakurani et al studied this specialty during the pandemic. They concluded that the escalating surge of plastic surgery cases in India was hit hard by the COVID-19 pandemic and that it would take a long time and serious actions to return to normalcy [14]. There are also several studies addressing the effects of this pandemic on variable specialties.…”
Section: Discussionmentioning
confidence: 99%
“…In India, Sangeeta Thakurani et al studied this specialty during the pandemic. They concluded that the escalating surge of plastic surgery cases in India was hit hard by the COVID-19 pandemic and that it would take a long time and serious actions to return to normalcy [14]. There are also several studies addressing the effects of this pandemic on variable specialties.…”
Section: Discussionmentioning
confidence: 99%
“…These data imply that there are many opportunities for the introduction of telemedicine after the pandemic in India. For example, the authors noted the need for the reprisal and legalization of teleconsultation in anesthetic surgery [27]. The country has to adopt proper implementation directives to ensure the success of telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, most Indian residents (up to 67% of the sample population) lived in rural destinations. In a study conducted by Thakurani and Gupta on 150 anesthetic surgeons in India, the COVID-19 pandemic forced these medical practitioners to transform and adapt their routines [27]. In Singapore, the incorporation of telemedicine in surgery during COVID-19 is likely to occur, as Bhaskar et al reported that its use of the service has increased during the pandemic [24].…”
Section: Telemedicine In Surgery Globallymentioning
confidence: 99%
“…Boardcertified surgeons should make an effort to increase their online visibility since social media is and will remain an integral part of the cosmetic surgery industry. Thakurani S, 2021 13 Evolution of aesthetic surgery in India, current practice scenario, and anticipated post-COVID-19 changes: a survey-based analysis.…”
Section: Retrospective Analysismentioning
confidence: 99%